Religious character education using a compassion approach: A case study at baitul qurro' wal huffadz darusshomad islamic boarding school - Siti Abidatul Mardiah; Muh. Wasith Achadi; Muhammad Shalahuddin Al Awwaby (At Turots: Jurnal Pendidikan Islam, 2024)
This article is a case study design using a critical analysis method oriented towards a qualitative approach. The problems in this article are first, what is the background of the establishment of the Baitul Qurro' Wal Huffadz Darusshomad tahfidz boarding school. Second, how are the forms of affection approach as one of the religious character education programmes of students at PONPES Baitul Qurro' Wal Huffadz Darusshomad. Third, what are the obstacles in implementing this form of affection in implementing religious character education. The results of this study are: First, the concern of the founder of the pondok pesantern related to the character and morals of teenagers around his residence who are still far away in Islamic law. Second, the form of compassion approach as one of the religious character education programmes implemented there are two kinds, namely by applying habituation in good speech and applying the principle of equality for all parties in the Baitul Qurro' Wal Huffadz Darusshomad boarding school environment, so that none of the santri feel discriminated against. Third, the obstacles felt by educators such as, children influencing each other's bad treatment, for example teaching their friends to smoke, skip class, or even the existence of seniority between them.